Edukacja medialna w rodzinie - Kosmalska , Beata (Studia Edukacyjne, 2019)
This article discusses issues of forming and developing media skills in children in a family setting. Research on the role of media (mainly television) in a child’s life has been conducted for many years and indicates a necessity to develop a child’s media skills early (Izdebska, 1996, 2007; Kossowski 1999; Braun-Gałkowska 2003). There is a shortage of data on the role of parents in preparing children for formal media education (at school or preschool). It is the parents’ responsibility to ensure that a child’s first contact with media is handled properly. In light of this, the following questions arise: Do parents know about the risks, and also opportunities, resulting from the use of media by children? Do they teach children how to choose which media to use and manage the amount of time spent doing it? Do they teach children proper ways of using media for play? I attempt answering these questions by referencing opinions of media experts, psychologists and educators on the topic of media influence (“media childhood”), the significance of media education in developing media literacy in children, and by presenting the conclusions of my research that inspire further insightful analyses into media education of children at home.